MAQORINAH BI ARAAU ANNAKHO’ AL-QADAMA WAL MUHDATSIIN: AL-MAF’UL ‘ENDA SIBAWAIHI - Husni, Arman (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2010)
The development of Arabic Grammar by time is not far from the figure of this science pioneer, Sibawaih (Abu Bisyr bin Usman bin Qunbur). From this age, the emergence of topics is in Nahwu. Among these topics that are always appearing is Al-Maf’ul. Even Sibawaih is regarded as pioneer in Nahwu, in fact, there are also many experts that are not in line with him, they are from Classic Nahwu (Al Qudama) or contemporer (Al Muhdatsun). Because the language is still develop in line with the time, then the topics of language also develop like Al-Maf’ul that is still relevant for reviewed by the reviewer of this science. There are many opinions about Al-Maf’ul that is in fact, what is Maf’ul Bih or Maf’ul Muthlaq or other. By the arguments appear for supporting each theory, sure will make us more critic to review deeper in language science that in time always change.